Establishment of NOD/SCID mouse models of human hepatocellular carcinoma via subcutaneous transplantation of histologically intact tumor tissue - Yan, Mingxia; Li, Hong; Zhao, Fangyu; Zhang, Lixing; Ge, Chao; Yao, Ming; Li, Jinjun (Chinese Journal of Cancer Research; Vol 25, No 3 (June 28, 2013): Chinese Journal of Cancer Research, 2013)
Hepatocellular carcinoma (HCC) is one of the most deadly human cancers, but it is very difficult to establish an animal model by using surgical specimens. In the present experiment, histologically intact fresh surgical specimens of HCC were subcutaneously transplanted in non-obese diabetic/severe combined immunodeficienccy (NOD/SCID) mice. The biological characteristics of the original and the corresponding transplanted tumors and cell lines were investigated. The results showed that 5 new animal models and 2 primary cell lines were successfully established from surgical specimens. Hematoxylin-eosin staining showed that xenografts retained major histological features of the original surgical specimens. The two new cell lines had been cultivated for 3 years and successively passaged for more than 100 passages in vitro. The morphological characteristics and biologic features of the two cell lines were genetically similar to the original tumor. The subcutaneous transplant animal models with histologically intact tumor tissue and primary cell lines could be useful for in vivo and in vitro testing of anti-cancer drugs and be ideal models to study various biologic features of HCC.